2018
DOI: 10.1108/ajim-01-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Linking personality traits and individuals’ knowledge management behavior

Abstract: Purpose Inspired by the theory of planned behavior, the purpose of this paper is to examine the impact of the big five personality (BFP) traits (openness, conscientiousness, extraversion, agreeableness, and neuroticism) on four aspects of individuals’ knowledge management (KM) behaviors: knowledge acquisition, knowledge storage, knowledge sharing, and knowledge application. Design/methodology/approach A survey-based approach was used to collect data from 221 employees from five knowledge-intensive firms. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 81 publications
6
28
0
3
Order By: Relevance
“…Individuals with healthy openness to experiences trait are always curious of new ideas, willing to participate in social interactions and have no issues with adopting new communication styles (Esmaeelinezhad and Afrazeh, 2018; Lynn et al , 2017; Stanton and Paolo, 2012). Results from this study showed that this trait had a definite relation to social networking.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Individuals with healthy openness to experiences trait are always curious of new ideas, willing to participate in social interactions and have no issues with adopting new communication styles (Esmaeelinezhad and Afrazeh, 2018; Lynn et al , 2017; Stanton and Paolo, 2012). Results from this study showed that this trait had a definite relation to social networking.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Knowledge transfer is represented by two constructs: knowledge acquisition and knowledge provision. Knowledge acquisition is the act of seeking and collecting work-related information and know-how within organizations (Esmaeelinezhad and Afrazeh, 2018;Wang and Noe, 2010). Yuan et al (2007) argued that employees acquire knowledge mainly from two kinds of sources within organizations: direct knowledge exchange with other individuals or knowledge extraction from knowledge repositories.…”
Section: Esm Affordances and Knowledge Transfermentioning
confidence: 99%
“…Akusisi pengetahuan dapat memperluas kapasitas pengetahuan individu dan memberikan kesempatan pada individu untuk memanfaatkan pengetahuan baru saat menyelesaikan tugas dan atau kewajiban yang harus dikerjakan (Rusly et al, 2015). Akuisisi pengetahuan juga berpengaruh terhadap keberhasilan individu untuk meningkatkan kapabilitas, kualitas individu, nilai kompetitif, dan kemampuan bersaing individu di dunia pendidikan maupun dunia kerja (Boateng et al, 2014;Esmaeelinezhad & Afrazeh, 2018)…”
Section: Pembelajaran Daringunclassified